scmt - SuperK Cluster Management Toolkit Plug-and-play management for single-board computer clusters - Åkerstedt Bergsten, Magnus; Bolin, Anders; Borgsten, Eric; Jonsson, Elvira; Lund, Sebastian; Olsson, Axel (My University, 2016)
Computer clusters have become increasingly important in elds such as high-performance computing and database management due to their scalability and lower economic cost compared with traditional supercomputers. However, computer clusters consisting of x86-based servers are expensive, highly power-consuming, and occupy signi cant space. At the same time, the availability of cheap but performant ARM-based single-board computers has steadily increased, with products such as Raspberry Pi and Odroid becoming competitive in performance with traditional servers. This report explores the creation of clusters using these devices, e.g. what bene ts and downsides there are compared to x86-clusters. In particular, lower economic cost and decreased power consumption are compelling bene ts. However, the subject of building clusters from ARM-devices is not a mature field, and there is a lack of tools and research on the subject. We present the SuperK Cluster Management Toolkit, a prototype software suite for managing clusters of single-board computers. In addition, we discuss problems particular to clusters of single-board computers and contrast different considerations in the design of cluster management software.
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Computer and Information Science; Information & Communication Technology